Optimasi Kondisi Depolimerisasi Pulp Biji Kakao - Ganda Putra; H Harijono; S Susanto; K Kumalaningsih; A Aulanni’am (Jurnal Teknik Industri, 2008)
Pulp breaking on cocoa processing could be conducted with depolymerization of cocoa pulp by enzyme polygalacturonase (PG) endogenous. This research was aimed to determination the optimum condition of depolymerization of cocoa pulp by enzyme polygalacturonase endogenous during incubation. This research was carried out by incubating cocoa pulp for 6 days on various of optimum condition of PG endogenous treatments, that is: temperature were 32.5o C, 37.5o C, 42.5o C, 47.5o C, 52.5o C and initial pH of pulp were 4.1; 4.6; 5.1, respectively. Optimum condition of depolymerization of cocoa pulp was determination by effectiveness test. Effectiveness test result, based on the highest effectiveness index, showed that the optimum condition of depolymerization of cocoa pulp was 47.5o C incubation temperature and 4,6 initial pH of pulp. Those treatment produced 18.29% of pulp liquid wieght total during 5 days incubation with average per day for pectin content, galacturonic acid content, acid total content, and the change of pH were 1.12%, 8.36%, 0.209 meq NaOH/g and 0,19 in cocoa pulp extract was incubated for 6 days, respectively.